Diffusion‐weighted imaging thermometry in multiple sclerosis. Issue 3 (31st October 2013) - Sai, Asari; Shimono, Taro; Sakai, Koji; Takeda, Akitoshi; Shimada, Hiroyuki; Tsukamoto, Taro; Maeda, Hiroko; Sakamoto, Shinichi; Miki, Yukio
<x xml:space="preserve">Abstract</x> Purpose To prospectively investigate brain temperature using MR diffusion‐weighted imaging thermometry in multiple sclerosis (MS) patients and age‐matched healthy controls, to examine comparisons of brain temperature between MS patients and healthy volunteers, and to examine correlations between brain temperature and disease duration and between brain temperature and Expanded Disability Status Scale (EDSS) in MS patients. Materials and Methods Thirteen MS patients and 13 age‐matched healthy controls were examined using a 3.0 Tesla MR unit from January 2011 to February 2013. Brain temperature in each participant was measured using diffusion‐weighted imaging‐based MR thermometry of the lateral ventricles. Group comparisons of brain temperature between MS patients and healthy controls were performed using the Student's t‐test. The determination of correlation between brain temperature in MS patients and disease duration, and between brain temperature and EDSS were performed using a Pearson's correlation coefficient test. For statistical analyses, values of P < 0.05 were considered statistically significant. Results Median brain temperature was 35.81°C (range, 35.06–37.03°C) in MS patients, and 36.29°C (range, 35.51–37.89°C) in healthy controls representing a significant difference (P = 0.020). No significant correlation of both between brain temperature and disease duration and between brain temperature and EDSS were identified (r/P = −0.382/0.198, −0.026/0.933). Conclusion Brain temperature was significantly lower in MS patients than in healthy controls, probably representing decreased brain metabolism in MS patients. J. Magn. Reson. Imaging 2014;40:649–654. © 2013 Wiley Periodicals, Inc.